Khula and the Role of the Judge in Perpetrating It in Light of the Amendments to the Iraqi Personal Status Law in The Kurdistan Region, A Comparative Analytical Study - Rahim, Bakhtyar Sidiq (Journal of Legal and Political Studies, 2014)
The Khula is one of the ways to end the relation partner when you realize the wife that it would be unable to continue to live with a man who doesn't love him, she afraid to break those border which was drawn by the God if it continue these relation marriage, because of she has prepared to return back those things which gave it to her husband like dowry, gifts , and may be done with the consent of the husband as in the Islamic jurisprudence, and without his consent as in a lot of comparative legislation, and this is cause to the final divorce. The modern laws of personal status (including the Law of amend the application Iraqi Personal Status Law No. 2008 issued by the Parliament of the Kurdistan Region of Iraq) authorizing the judge to differentiate between the wife and husband by khul if the wife that the is demanded although the husband refuses to respond to the request, if the judge is satisfied the wife can not live with him through two arbitration between them, the wife return back .
Keywords: Marriage; Iraqi Personal Status Law; Comparative legislation; Consent